LINGKUNGAN PENGENDAPAN FORMASI MALAWA, SULAWESI SELATAN BERDASARKAN KANDUNGAN MAKRO FOSIL - Fauzie Hasibuan (Pusat Survei Geologi, 2009)
The study of molluscs from the Malawa Formation revealed the paleoenvironmental deposition of the formation. Four measured stratigraphic sections which are representastive of the formation contain well preserved molluscan fauna. The results of analysis indicate that the Malawa Formation of Middle Eocene age has been deposited in a mangrove environment, near shore, high energy, with fresh water influx such as rivers, in a lagoon with sand bars, a kind of deltaic environment.Â Keywords: Malawa Formation, Middle Eocene, molluscs, mangrove, deltaic environment